TEACHING PRONUNCIATION WITH THE HELP OF MODERN TECHNOLOGY - Dagarov Sodiq Murtoza o‘g‘li; Mamasidiqov Muhammadjon Saidmurod o’g’li; Maxramov Ozodbek Shavkat o’g’li (TADQIQOTLAR, 2026)
Annotation This article explores the role of modern technology in teaching pronunciation in language learning. It emphasizes that correct pronunciation is essential for effective communication and helps learners speak more clearly and confidently. The article examines various technological tools such as mobile applications, speech recognition software, online videos, and virtual learning platforms. These tools allow students to listen to native speakers, practice pronunciation repeatedly, and receive immediate feedback on their performance. Furthermore, the article discusses how technology creates an interactive and flexible learning environment. It also highlights the important role of teachers in guiding students and supporting the effective use of technology. In conclusion, modern technology makes pronunciation learning more engaging, accessible, and efficient.